2015
DOI: 10.4103/0300-1652.160401
|View full text |Cite
|
Sign up to set email alerts
|

A five year audit of mammography in a tertiary hospital, North Central Nigeria

Abstract: Background:Breast imaging plays a vital role in the multidisciplinary approach to management of breast disease. A baseline data is apt and necessary for collaborative studies.Materials and Methods:This is a prospective descriptive study carried out between January 2009 and December 2013 at our institution. Patients who had breast imaging were recruited into the study. Film-screen mammograms were acquired with a General Electric (GE) Senographe DMR machine. Breast ultrasound done using an Aloka Prosound SSD-350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
3
16
2
Order By: Relevance
“…Of these benign lesions, the most frequently diagnosed were fibroadenoma, followed by breast cysts. Most breast lesions had been reported to be benign in previous studies (1,2,3,14,15), this is in tandem with our finding which also reported that fibroadenoma of the breast was more prevalent than other breast lesions, though some studies had postulated other breast lesions such as fibrocystic diseases to be commoner (2). The characteristics malignant breast features we encountered in this study were dense breast mass with irregular, multilobular and spiculated margins which may be poorly defined.…”
Section: Discussionsupporting
confidence: 91%
“…Of these benign lesions, the most frequently diagnosed were fibroadenoma, followed by breast cysts. Most breast lesions had been reported to be benign in previous studies (1,2,3,14,15), this is in tandem with our finding which also reported that fibroadenoma of the breast was more prevalent than other breast lesions, though some studies had postulated other breast lesions such as fibrocystic diseases to be commoner (2). The characteristics malignant breast features we encountered in this study were dense breast mass with irregular, multilobular and spiculated margins which may be poorly defined.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, few males were reported to have undergone diagnostic mammography in some parts of Nigeria [2,14] in contrast to most other studies that had only female participants [1,13,16,17,19]. This underscores the fact that breast diseases are not exclusive to females, though the incidence of breast cancer in males is very low.…”
Section: Discussioncontrasting
confidence: 47%
“…Some studies have reported on the mammographic findings in different parts of the country [1,2,[13][14][15][16][17][18][19]. About half of the participants in this study were within the age group 40-49 years.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations